Japanization what the world can learn from Japan's lost decades - Pesek, William (Singapore Bloomberg Press, an imprint of Wiley, 2014)
An in-depth look at Japan's economic malaise and the steps it must take to compete globally. In Japanization, Bloomberg columnist William Pesek-based in Tokyo-presents a detailed look at Japan's continuing twenty-year economic slow-down, the political and economic reasons behind it, and the policies it could and should undertake to return to growth and influence. Despite new Prime Minister Shinzo Abe's promise of economic revitalization, investor optimism about the future, and plenty of potential, Japanization reveals why things are unlikely to change any time soon.
Chapter 1: How Japan Papers Over Economic Cracks with Monetary and Fiscal Policy -- Chapter 2: The Female Problem: How Institutionalized Sexism Kills Growth -- Chapter 3: The 1,000,000,000,000,000 Yen Monster: When a Debt Market Becomes So Big It Dominates Everything -- Chapter 4: The Fukushima Effect: How Rampant Cronyism Holds Japan Back -- Chapter 5: Galapagos Nation: How Isolation Stunts Japan's Evolution -- Chapter 6: Hello Kitty Isn't a Foreign Policy: How Amateurish Diplomacy Undermines Japan -- Chapter 7: Will Abenomics Save the World?
Includes bibliographical references and index.
Keywords: Globalization; Japan -- Economic policy; Japan -- Politics and government -- 21st century